STEP BY STEP DESCRIPTION OF PHYSICAL QUALITIES IN VOLLEYBALL TRAINING - Ruziyev Sherzod (Academia Science Repository, 2023)
Volleyball is the most popular sport in the world, second only to football. Volleyball is a competitive sport with a competitive spirit that can make players and their families want to win. It is described as a creative combination of other familiar sports such as tennis, basketball, handball and baseball. Starting a volleyball club can be fun, but it’s also hard work. The article offers suggestions and recommendations regarding the importance of organizing volleyball clubs in higher education institutions.